Pengaruh Profitabilitas, Growth Opportunity, Capital Structure Dan Size Terhadap Nilai Perusahaan Real Estate Dan Property Yang Terdaftar Di BEI Tahun 2018-2021 - Rafly Zidane; Titiek Suwarti (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to examine and analyze the effect of profitability, growth opportunity, capital structure, and size on firm value in property and real estate companies listed on the Indonesia Stock Exchange in 2018-2021. The sampling method used in this research is using purposive sampling technique and obtained a sample of 246 companies. The data analysis method used in this research is multiple linear regression analysis. The results showed that growth opportunity had a significant positive effect on firm value, while capital structure had a significant negative effect on firm value. However, profitability and size have no effect on firm value. Keywords : Profitability, Growth Opportunity, Capital Structure, Size, Firm Value